Efeito do CPAP no estresse oxidativo e na qualidade de vida em adultos e idosos com síndrome da apnéia obstrutiva do sono - Yagihara, Fabiana Tokie [UNIFESP] (2010)
Introduction: The effects of intermittent hypoxia and hypercapnia resulting from obstructive respiratory events Syndrome Obstructive Sleep Apnea (OSAS) in the generation of reactive oxygen species (ROS) has recently received particular attention because of its association with oxidative stress (OS) and aging process. Although the literature highlights the positive effects of Continuous Positive Air Pressure (CPAP) in sleep patterns, excessive daytime sleepiness and OS in adults are rare studies in the elderly. The aim of this study was to evaluate the effects of OS parameters in elderly patients, comparing them with an adult population and investigate the effect of CPAP treatment in elderly patients with OSAS and the impact on their quality of life. Methods: We selected individuals between 25 to 75 years old and divided into four groups: elder OSAS, elder controls, adult OSAS and adult controls. For the elderly group, 30 volunteers were selected with OSAS and 27 control volunteers matched for age. Data from 13 adult volunteers with OSA and 12 without OSA were used to compare with the elderly only at baseline. This study was prospective and comparative study between the group of elderly volunteers without OSA and the group of elderly patients with OSAS. The analysis was also made before and after use of CPAP for the OSAS group. All night polysomnography was used to determine sleep-disordered breathing AHI and the subsequent division of the groups. Questionnaires were applied to evaluate the subjective excessive daytime sleepiness (Epworth Sleepiness Scale) and quality of life (SF-36). Laboratory tests were conducted to evaluate parameters related to oxidative stress: allantoin, vitamin B12, folic acid, vitamin E, vitamin C, lipid peroxidation, catalase, superoxide dismutase, homocysteine and cysteine. A comparison was made between adults and elders and to evaluate the effect of CPAP in the elderly patients by means of appropriate statistical tests. Results: In the comparison between adults and elder, the levels of vitamin E, elder OSAS (22.2 ± 1.9 umol / L) had higher levels than the adult OSAS group (12.7 ± 1.7 umol / L) and elderly control (26.5 ± 1.7 umol / L) and adult control (19.2 ± 1.8 umol / L) showing an interaction of time and OSAS in the variable. As for the homocysteine levels, the adult OSAS group (17.2 ± 1.3 mmol / L) had higher levels than adult control (10.8 ± 1.4 mmol / L). In elderly patients with OSAS, CPAP treatment showed reversal of oxidative stress by decreasing lipid peroxidation expressed by the amount of malondialdehyde (MDA) [pre: 2.7 (95% 1,6-3,7) vs. post: 1.3 (0.7-1.9), p <0.01]. Treatment with CPAP in this group improved two areas of the questionnaire of quality of life SF-36: Functional Capacity [pre = 77.4 (69,2-85,5) vs. post = 83.4 (76,9-89,9), p = 0.04] and pain [pre = 65.4 (52,8-78,1) vs. post = 77.8 (67,2-88,3), p = 0.005]. Conclusion: Our study showed showed that adult OSAS group showed a reduction in the levels of vitamin E, indicating a reduction of antioxidant capacity compared to the older group (OSAS and control), suggesting that adults react heterogeneously to the effects of stress (intermittent hypoxia and reoxygenation) compared with the elderly. Treatment with CPAP in elderly patients with OSAS contributed to the reversal of oxidative stress by decreasing levels of MDA and improving the quality of life.